Prevalence of nocturnal hypoglycemia in free-living conditions in adults with type 1 diabetes: What is the impact of daily physical activity? - Molveau, Joséphine; Rabasa-Lhoret, Rémi; Myette-Côté, Étienne; Messier, Virginie; Suppère, Corinne; J. Potter, Kathryn; Heyman, Elsa; Tagougui, Sémah (Frontiers in Endocrinology, 2022)
Objective: Studies investigating strategies to limit the risk of nocturnal hypoglycemia (NH) associated with physical activity (PA) are scarce and have been conducted in standardized, controlled conditions in people with type 1 diabetes (T1D). This study sought to investigate the effect of daily PA level on nocturnal glucose management in real-life conditions while taking into consideration reported mitigation strategies to limit the risk of NH in people with T1D. Methods: Data from 25 adults (10 males, 15 females, HbA1c: 7.6±0.8%), 20-60 years old, living with T1D, were collected. One week of continuous glucose monitoring and PA (assessed using an accelerometer) were collected in real-life conditions. Nocturnal glucose values (midnight–6:00 am) following active day “ACT” and inactive day “INA” were analyzed to assess the time spent within the different glycemic target zones between conditions. Self-reported data about mitigation strategies applied to reduce the risk of NH was also analyzed. Results: Only 44% of participants reported applying a carbohydrate- or insulin-based strategy to limit the risk of NH on ACT day. NH occurrences were comparable on ACT night versus on INA night. Additionnal post-meal carbohydrate intake was higher on evenings following ACT (19.5 ± 11.0, INA vs. 27.7 ± 15.6, ACT; P=0.045), but was frequently associated with an insulin bolus. NH the night following ACT occurred mostly in people who administrated an additional insulin bolus before midnight (3 out of 5 participants with NH). Conclusions: Although people with T1D seem to be aware of the increased risk of nocturnal hypoglycemia associated with physical activity, the risk associated with additional insulin boluses may not be as clear. Most participants did not report using compensation strategies to reduce the risk of exercise related late-onset hypoglycemia which may be because they did not consider habitual PA as something requiring treatment adjustments.